Studi Optimasi Waktu dan Biaya dengan Metode Time Cost Trade Off pada Proyek Konstruksi Pembangunan Gedung Olah Raga (Gor) - Priyo, Mandiyo; Paridi, Meiki Risa Anggriani (Semesta Teknika, 2018)
Cost and time analysis are most important on the contruction project. Optimal Time and minimal cost become standart to make profit benchmarks on a project. Therefore, it is necessary to optimize the cost and time by looking for work items that are included in the critical path. The purpose of this study is to know the change of cost and time due to the addition of working time, change of cost and time due to the addition of employee, as well as cost that needed if the projects experienced delays and penalty.. So it will be compared from all three to get the minimum cost with the optimum duration.The data used in this study is secondary data obtained from contractor implementing. Data analysis using time cost trade off method with microsoft project 2010 program. The results of the study, From the time cost trade off with the addition of 1 hours of work per day conducted on first day on critical jobs during the project, obtained the reduction in the cost of Rp 39,552,394,71 and the reduction in the duration of 36.18 days. Addition of 2 hours of work per day obtained the reduction in the cost of Rp 57,532,834.66 and and the reduction in the duration of 62.61 days. Addition of 3 hours of work per day obtained the reduction in the cost of Rp 69,392,147,01 and and the reduction in the duration of 82.48 days. Meanwhile, for the addition of employee for 1 hours obtained the reduction in the cost of Rp 52.497.085,35 and the reduction in the duration of 36.18 days. Addition of employee for 2 hours obtained the reduction in the cost of Rp 91,349,394.80 and the reduction in the duration of 62.61 days. Addition of employee for 3 hours obtained the reduction in the cost of Rp 120,645,301,55 and the reduction in the duration of 82,48 days. So that, the optimal time and cost occur when addition employee is incurred for 3 hours, compared to overtime and overdue. Namely with the optimal cost of the project of Rp 2,418,408,305.45 and the optimal duration of the project for 57.52 days.